SIFAT FISIK, KIMIA DAN MIKROORGANISME PADA BIOAKTIVATOR MOL KOMBINASI Physical Nature, Chemical and Microorganism on The Combination of MOL Bioaktivator - Riama Rita Manullang; Rusmini; Daryono (JURNAL AGRIMENT, 2017)
The role of MOL as a basic component of fertilizer, microorganisms not only beneficial to plants are also useful asdecomposers agents of organic materials, agricultural waste, household waste and industry. The rapidly growingdecomposer in organic farming systems is utilizing local microorganisms (MOL). Local microorganisms (MOL) aremicroorganisms that are used as starter in the manufacture of solid organic fertilizer and liquid fertilizer. The mainingredient of MOL consists of several components, namely carbohydrates, glucose, and microorganism sources.This study is based on the amount of untreated fruit waste, banana cultivation waste that is left to accumulatewithout being treated more useful, the golden snail is always considered a pest on crops and cattle rumen arewasted and efforts to overcome dependence on chemical fertilizers and pesticides can be done by increasing therole of microorganisms. The objective of this research is to produce mole solution which can be used as bioactivatorand as organic liquid and microorganism found in mole. . The materials used in the manufacture of MOL are bananasticks, fruit waste, golden snail, cow rumen, cow urine, coconut water, rice laundry water (lery), terasi, brown sugarfor MOL I whereas For MOL II only distinguished by using sugar white. Mole made by fermentation MOL Makingdone in Laboratoriuam Production of State Agricultural Polytechnic of Samarinda. The result of physical observationof the moles performed every day on the 10th day of the mole is already so / ripe based on the followingcharacteristics when kissed mole has no odor or smell of tape, there is a change of color from brown to dark brownand the state of temperature which has stabilized three days in a row. On the surface of the mole there are whitethreads on the surface of the mole. Based on the chemical analysis of nutrients in the mole is still low. As for theidentification of microorganisms in bioactivators in combination MOL I there are 4 types of bacteria, namelyClavibacter, Agrobacterium, Clostridium, Pseudomonas berfluorescens, while for MOL II there are 3 types ofpessimus ie Pseudomonas berkluorescens, Erwinia and Clavibacter